The impact of rheumatoid foot on disability in Colombian patients with rheumatoid arthritis (2009)
Background. Alterations in the feet of patients with rheumatoid arthritis (RA) are a cause of disability in this population. The purpose of this research was to evaluate the impact that foot impairment has on the patients' global quality of life (QOL) based on validated scales and its relationship to disease activity. Methods. This was a cross-sectional study in which 95 patients with RA were enrolled. A complete physical examination, including a full foot assessment, was done. The Spanish versions of the Health Assessment Questionnaire (HAQ) Disability Index and of the Disease Activity Score (DAS 28) were administered. A logistic regression model was used to analyze data and obtain adjusted odds ratios (AORs). Results. Foot deformities were observed in 78 (82%) of the patients; hallux valgus (65%), medial longitudinal arch flattening (42%), claw toe (lesser toes) (39%), dorsiflexion restriction (tibiotalar) (34%), cock-up toe (lesser toes) (25%), and transverse arch flattening (25%) were the most frequent. In the logistic regression analysis (adjusted for age, gender and duration of disease), forefoot movement pain, subtalar movement pain, tibiotalar movement pain and plantarflexion restriction (tibiotalar) were strongly associated with disease activity and disability. The positive squeeze test was significantly associated with disability risk (AOR = 6,3; 95% CI, 1.2830.96; P = 0,02); hallux valgus, and dorsiflexion restriction (tibiotalar) were associated with disease activity. Conclusion. Foot abnormalities are associated with active joint disease and disability in RA. Foot examinations provide complementary information related to the disability as an indirect measurement of quality of life and activity of disease in daily practice. © 2009 Rojas-Villarraga et al; licensee BioMed Central Ltd.